Innovating Bacterial Cultivation Practicums to Promote Deep Learning: A Trial and Reconstruction of Student Worksheets (LKPD) - Afifi Mutiarani; Amprasto; Kusnadi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate and test the feasibility of a student worksheet (LKPD) on bacterial cultivation and observation from a Natural Science textbook for grade X senior high school as a means to foster deep learning in the context of the deep learning. Using the Vee Diagram approach, the analysis shows that the LKPD contains several fundamental shortcomings—particularly in its unclear learning objectives, unsystematic procedures, and minimal space for reflection and data transformation. Through a self-conducted practicum trial, these identified weaknesses were indeed reflected in field implementation. Although the practicum was conducted, it faced issues such as overly dense colony growth, contamination, and inappropriate inoculation techniques, which led to suboptimal observations. This confirms that the structure and instructions in an LKPD significantly influence the success of experimental learning. Nonetheless, the activity revealed potential for further development. The practicum offers students the opportunity to experience scientific processes firsthand and understand the connection between biological concepts and real-life phenomena. With improved structure and approach, the LKPD can serve as an effective tool to support deep learning.